The Effect of Good Corporate Governance on Profit Management (Case Study: Transportation Companies Listed on the IDX) - Oktarini Khamilah Siregar; Alditra Dwiky Junidwan (Proceeding of The International Conference on Economics and Business, 2022)
Financial statements have the objective of presenting information related to financial condition and position, performance and changes in financial position that provide benefits to a large number of users of financial information, particularly profits that have been obtained. Finance is information that shows the company's achievement in generating profits. Earnings information is a part / component of the company's financial statements that aims to inform management performance, helping to estimate representative earnings capacity in the long term. This study aims to determine the effect of Independent Commissioners, Audit Committee, Institutional Ownership, Auditor Quality and Profitability on earnings management in transportation companies listed on the Indonesia Stock Exchange. This type of research is a causal quantitative research located on the Indonesia Stock Exchange (IDX) which is accessed through www.idx.co.id with a sample size of 5 companies during the 2015-2019 period using panel data linear regression analysis. The results showed that through the Chow and Hausman tests the fixed effects model (FEM) was used. The results of the t test show that partially the Independent Commissioner, Audit Committee, Institutional Ownership, Auditor Quality have an effect on Earning Management. Simultaneously the Independent Commissioner, Audit Committee, Institutional Ownership, Auditor Quality have an effect on Earnings Management.